Dietary management of obesity and type 2 diabetes: What advice should we be giving? - Dyson, P (Omnia-Med Ltd, 2017)
There are a variety of strategies that can be used to induce weight loss in people with diabetes, and evidence suggests that significant weight losses occur with most diets, and that differences between different diets are small and insignificant (Johnston et al, 2014; Naude et al, 2014). To optimise weight loss, it is recommended that primary care practitioners support their patients with a dietary strategy of their choice and agree realistic weight loss targets.